Orientaciones para la transición del sistema de gestión de la calidad basado en la norma ISO/IEC 17025:2005 a la ISO/IEC 17025:2017 en un laboratorio de ensayo de control al dopaje (2020)
This work presents practical guidelines for the transition and updating of the quality management system from the ISO / IEC 17025: 2005 standard to the ISO / IEC 17025: 2017 standard, in a doping control test laboratory. The doping control test laboratories in the world are in charge of carrying out the controls for the detection of prohibited substances in athletes, by means of analysis of the collected biological samples. Given the importance of these analyzes, the laboratory requires accreditation by the regulatory entities of the control test laboratories to doping WADA and ONAC, in order to guarantee technical competence and validity in the results.